ENHANCING STUDENTS’ MOTIVATION AND READING ACHIEVEMENT TROUGH HYPNOTEACHING METHOD IN CLASS XI STUDENTS - Muhammad Zainuddin (Journal of English Educational Study (JEES), 2019)
This research aims to find out (1) the influence of using the Hypnoteaching method in improving students’ motivation, (2) the influence of using the Hypnoteaching method towards students’ reading achievement and (3) the influence of using the Hypnoteaching method in enhancing students’ motivation and reading achievement. This is quasi-experimental research with the pre-test and post-test control group design. This research was conducted at class XI students in Madrasah Aliyah Negeri Unggul Tenggarong in the period of 2015/2016. The data were collected using tests and non-test. The data were analyzed by using the Multivariate Analyses of Variance (MANOVA) at the significance level of 95 % (p=0.05). The results of this research are as follows. (1) There is an influence of students’ learning motivation after teaching by using the Hypnoteaching method. There is a significant difference in students’ reading achievement after teaching by using the Hypnoteaching method. The Hypnoteaching method affects students’ achievement in reading and student’s learning motivation after getting treatment, the data of Wilks’Lambda have a significance (F-value = 6.963) and sig = 0.02< 0.